Women's autonomy in household decision-making and safer sex negotiation in sub-Saharan Africa: An analysis of data from 27 Demographic and Health Surveys - Abdul-Aziz Seidu; Richard Gyan Aboagye; Joshua Okyere; Wonder Agbemavi; Mawulorm Akpeke; Eugene Budu; Farrukh Ishaque Saah; Vivian Tackie; Bright Opoku Ahinkorah (Elsevier, 2021)
Women's ability to negotiate the conditions and timing of sex is key to several reproductive health outcomes including family planning and prevention of sexually transmitted infections. We investigated the association between women's autonomy in household decision-making and safer sex negotiation (SSN) in sub-Saharan Africa (SSA). This was a cross-sectional analysis of data from the Demographic and Health Survey (DHS) of 27 countries in SSA. Data were analyzed using Stata version 16.0 using descriptive statistics, chi square test, and logistic regression models. Statistical significance was set at p < 0.05 at 95% confidence interval. The pooled prevalence of SSN in the 27 countries was 77.1%. Compared to women with low autonomy in household decision-making, those with medium (aOR = 1.30; CI = 1.23-1.37) and high levels of autonomy in household decision-making (aOR = 1.28; CI = 1.17-1.40) were more likely to have greater SSN. Those with primary (aOR = 1.35; CI = 1.28-1.41) and secondary/higher education level of education (aOR = 1.68; CI = 1.58-1.79) had higher odds of SSN, compared to those with no formal education. Women who were working had higher odds of SSN (aOR = 1.44; CI = 1.37-1.51) than those who were not working. Women in the middle (aOR = 0.93; CI = 0.87-0.99) and richer (aOR = 0.92; CI = 0.85-0.98) wealth status had lower odds of SSN, compared to those in the poorest wealth status. Women's autonomy in household decision-making is a significant predictor of SSN. Women autonomy in household decision-making programs and interventions should be intensified to achieve Sustainable Development Goals 3.7 and 5 which seek to achieve universal access to sexual and reproductive health services and ensure gender equality and empower all women and girls by 2030.